VALIDATION OF HEADSPACE SOLID-PHASE MICROEXTRACTION WITH GAS CHROMATOGRAPHY-FLAME IONISATION DETECTOR METHOD FOR ALCOHOL ANALYSIS ON GASTRIC FLUID - Thaiyibah, Nazaratun; Yuwono, Mochammad; Yudianto, Ahmad (Jurnal Kimia Riset, 2023)
Identifying the concentration of alcohol compounds in postmortem analysis of biological fluids can help the investigation, just as postmortem analysis of gastric juices can reveal the concentrations of alcohol consumed. However, an efficient and effective combination of extraction and measurement methods is required when looking at complex postmortem samples. Therefore, a headspace-solid phase microextraction (HS-SPME) method was developed using gas chromatography with a flame ionization detector (GC-FID) to identify postmortem alcohol concentrations. This present study optimizes and validates an effective and efficient method for postmortem alcohol extraction and quantification in gastric fluid. The optimal conditions for HS-SPME extraction using 65Î¼m Polydimethy lsiloxane Divinyl benzene (PDMS/DVB) fiber for analyte isolation were 15 minutes. at 60°C and an exposure time of 1 minute. The validation investigation shows that the suggested approach satisfies the criteria for linearity, precision, accuracy, LOD, and LOQ for postmortem measurement of alcohol in gastric fluid.